2021
DOI: 10.1186/s13229-021-00424-y
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of the COVID-19 pandemic on adults with autism: a survey study across three countries

Abstract: Background Previous studies have reported a negative psychological and mental health impact of the COVID-19 pandemic. This impact is likely to be stronger for people with autism as they are at heightened risk of mental health problems and because the pandemic directly affects social functioning and everyday routines. We therefore examined COVID-19 pandemic-related changes in mental health, the impact of the pandemic on their social life and routines, satisfaction with pandemic-related informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
2
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 47 publications
12
124
2
9
Order By: Relevance
“…Moreover, some studies have reported positive effects of the COVID-19 pandemic on the mental health of autistic adults ( 8 , 15 , 27 , 28 ). Positive outcomes and coping strategies reported by autistic adults include being able to use extra time to pursue hobbies, establishing new routines, spending more time with family, keeping busy engaging in chores, adapting to virtual social connexion, spending time in nature and learning at a comfortable pace ( 15 , 27 ). Spending time outdoors “in nature” has more generally been promoted as an effective adaptive strategy during the pandemic ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, some studies have reported positive effects of the COVID-19 pandemic on the mental health of autistic adults ( 8 , 15 , 27 , 28 ). Positive outcomes and coping strategies reported by autistic adults include being able to use extra time to pursue hobbies, establishing new routines, spending more time with family, keeping busy engaging in chores, adapting to virtual social connexion, spending time in nature and learning at a comfortable pace ( 15 , 27 ). Spending time outdoors “in nature” has more generally been promoted as an effective adaptive strategy during the pandemic ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…By Time 3, 36.14% of participants reported the impact of COVID-19 worsening pre-existing mental health conditions; 53.68% reported feeling more anxious; and 48.6% reported feeling more depressed than before the pandemic. For example, Oomen et al, ( 8 ) found an increase in depression and anxiety symptoms in response to the pandemic for autistic adults, participants also showed a greater interest in worries about pets, work, access to medication and food compared to non-autistic peers. Therefore, although there may have been some positive impact on sleep in autistic adults, the overall impact of the pandemic on mental health and sleep, and complex interactions between these two factors, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation and loneliness were the main barrier identified by typical teenagers in a study by Tardif-Grenier et al (2021) with a sample from the same area as the one in our study. Oomen et al (2021) reported more drastic changes for non-autistic persons than for autistic persons regarding their "social life" (p. 13). Furthermore, it is not surprising that the caregivers and families of autistic children in our study felt isolated during the pandemic, as this was reported by others as well (more than 70% of the sample in Salt et al, (2020).…”
Section: The Need For Social Interactionsmentioning
confidence: 99%